Search for lepton-flavour-violating decays of Higgs-like bosons - Aaij, Roel; Abellán Beteta, C.; Adeva, Bernardo; Adinolfi, Marco; Aidala, Christine A.; Ajaltouni, Ziad J.; Akar, Simon; Albicocco, Pietro; Albrecht, Johannes; Alessio, Federico; Alexander, Michael T.; Alfonso Albero, A.; et al. (The European physical journal. C, Particles and fields, 2018)
A search is presented for a Higgs-like boson with mass in the range 45 to 195GeV/c2GeV/c2\,{{GeV/}c^2} decaying into a muon and a tau lepton. The dataset consists of proton-proton interactions at a centre-of-mass energy of 8 TeV TeV~TeV, collected by the LHCb experiment, corresponding to an integrated luminosity of 2 fb −1 fb −1\,\text{ fb }^{-1}. The tau leptons are reconstructed in both leptonic and hadronic decay channels. An upper limit on the production cross-section multiplied by the branching fraction at 95% confidence level is set and ranges from 22pbpb\,{pb} for a boson mass of 45GeV/c2GeV/c2\,{{GeV/}c^2} to 4pbpb\,{pb} for a mass of 195GeV/c2GeV/c2\,{{GeV/}c^2}.
LHCb Collaboration: R. Aaij, C. Abellán Beteta, B. Adeva, M. Adinolfi, C. A. Aidala, Z. Ajaltouni, S. Akar, P. Albicocco, J. Albrecht, F. Alessio, M. Alexander, A. Alfonso Albero, G. Alkhazov, P. Alvarez Cartelle, A.A.Alves Jr, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 13.06.2019